Cleanliness and Health Of Pa.So.La Kitchen, The Ritz Carlton Jakarta Pacific Place - Auliya, Anisatul; Prianti, Diani; Fajrin, Annisa Nurul (Universitas Terbuka, 2024)
By implementing good hygiene and sanitation practices, employees can carry out their duties efficiently and produce high-quality food in Pa.So.La Kitchen, The Ritz-Carlton Pacific Place Hotel, which aligns with the hotel's motto,